URGENSI PENDAMPINGAN OLEH ADVOKAT DALAM PENYIDIKAN PERKARA PIDANA : Studi terhadap Penyidikan Tindak Pidana Pembunuhan Ibu dan Anak di Kota Kupang - Kapitan, Rian Van Frits (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Randy Badjideh was officially named a suspect by East Nusa Tenggara Regional Police investigators on December 2 2021 in the case of the murder of a mother and child in Kupang City. Randy Badjideh immediately appointed several advocates to accompany him when he was questioned as a suspect. However, there were many insults towards the Advocate Team accompanying Randy Badjideh. Therefore, the formulation of the problem in this paper is whether it is urgent for Randy Badjideh to be accompanied by an advocate in the investigation process? The purpose of this article is to determine the urgency for Randy Badjideh to be accompanied by an advocate in the investigation process. The research method used in this paper is normative juridical research which focuses on several approach methods, namely the case approach method, conceptual approach method and statutory approach method. The conclusions obtained regarding the urgency for Randy Badjideh to be accompanied by an Advocate in the investigation process are: first, Randy Badjideh must always be accompanied by an Advocate when being questioned as a suspect. Second, without being accompanied by an Advocate when being examined, the examination will be invalid and result in being null and void. Third, if the examination of Randy Badjideh is null and void, all of Randy Badjideh's confessions regarding the murder of Astrit and Lael Maccabee will be deemed to have never existed, so that it will dim the disclosure of the murder case which he has been working hard to uncover since the beginning. Fourth, investigators who carry out examinations of Randy Badjideh without being accompanied by an advocate may be subject to code of ethics sanctions which will result in him being removed from his position as an investigator.